Potensi Trigonelline Ekstrak Biji Kopi Robusta Sebagai Agen Antiinflamasi Periodontitis: Studi In Silico - Alifa Nukhi Nur Rokhmah (FAKULTAS KEDOKTERAN GIGI, 2026)
Periodontitis is a chronic inflammatory disease that damages the tissues supporting the gingiva and the alveolar bone. This disorder involves complex interactions between the immune system and bone metabolism through osteoimmune pathways. RUNX2, RANK, and RANKL are crucial proteins that regulate osteoblast differentiation and osteoclast production during bone remodelling. Trigonelline, a natural chemical derived from robusta coffee extract (Coffea canephora), is a promising candidate for interaction with osteoimmune target proteins (RUNX2, RANK, RANKL) via an in silico molecular docking methodology. This work seeks to evaluate the capacity of trigonelline to engage with the proteins RUNX2, RANK, and RANKL via an in silico molecular docking methodology. The three-dimensional structures of trigonelline ligands, control ligands, and target proteins were acquired from PubChem (NCBI) and The Research Collaboratory for Structural Bioinformatics Protein Data Bank (RCSB PDB). Molecular docking was subsequently conducted via PyRx to get binding affinity values and visually analyse the interaction types (hydrogen bonds and van der Waals interactions) with Discovery Studio. pkCSM was used to predict the pharmacokinetic properties of the compound, and oral toxicity prediction was carried out using ProTox 3.0. The docking results indicated that trigonelline exhibited interactions with proteins demonstrating the highest binding affinities: RANK (-4.9 kcal/mol), RANKL (-4.8 kcal/mol), and RUNX2 (-4.7 kcal/mol). Van der Waals interactions and hydrogen bonds with amino acid residues encircling the protein binding site indicate a specific and structurally stable binding region. Pharmacokinetic prediction showed good results while oral toxicity showed that the trigonelline belonged to toxicity class 5. The findings suggested that trigonelline may serve as a bioactive molecule that interacts with osteoimmune proteins (RUNX2, RANK, RANKL) implicated in bone remodelling and inflammation, as demonstrated by the in silico molecular docking analysis. Additionally, in vitro and in vivo investigations are required to corroborate these results.
Validasi file repository 11 Juni 2026_Magang SP(Anugrah Duta)_Firli
Keywords: trigonelline; periodontitis; molecular docking; in silico